Lion heart : a Scarlet novel - Gaughen, A. C. (Gaughen, A. C. Scarlet novel., 2015)
After escaping Prince John's clutches and longing to return to Rob in Nottingham, Scarlet learns that King Richard's life is in jeopardy and accepts Eleanor of Aquitaine's demand that Scarlet spy for her and help bring Richard home safe.